Tłumaczenie Winnie-the-Pooh na język górnołużycki (w kontekście przekładów na język polski i czeski. - Szpila, Grzegorz (Slavia Occidentalis, 2014)
The paper discusses the translation of Winnie-the-Pooh into Upper-Sorbian (Winij Pu). Its aim is to present and assess the translation of proper names in the Upper-Sorbian version by Edward Wornar. The author compares the strategies and techniques used by the translator with those deployed in the Polish and Czech translations of the book. The examination of Wornar’s version demonstrates that the translator used many a domestication technique. The translation under scrutiny is positively evaluated as it wisely utilizes various available strategies and techniques to render the original text accessible and acceptable to the target language and culture.